2006
DOI: 10.1111/j.1574-6976.2006.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the IncW genetic backbone imply general trends in conjugative plasmid evolution

Abstract: Plasmids cannot be understood as mere tools for genetic exchange: they are themselves subject to the forces of evolution. Their genomic and phylogenetic features have been less studied in this respect. Focusing on the IncW incompatibility group, which includes the smallest known conjugative plasmids, we attempt to unveil some common trends in plasmid evolution. The functional modules of IncW genetic backbone are described, with emphasis on their architecture and relationships to other plasmid groups. Some plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 149 publications
6
150
1
2
Order By: Relevance
“…Relaxosome formation requires two auxiliary proteins, plasmid‐encoded TrwA, and host‐encoded IHF. trwN‐D and trwABC are located in two operons, the expression of which is coordinated by three distinct promoters (de Paz et al , 2005; Fernandez‐Lopez et al , 2006). For clarity, we will use both the “Trw” and “VirB” nomenclatures.…”
Section: Resultsmentioning
confidence: 99%
“…Relaxosome formation requires two auxiliary proteins, plasmid‐encoded TrwA, and host‐encoded IHF. trwN‐D and trwABC are located in two operons, the expression of which is coordinated by three distinct promoters (de Paz et al , 2005; Fernandez‐Lopez et al , 2006). For clarity, we will use both the “Trw” and “VirB” nomenclatures.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies of isolates from different genera or different parts of the world (Norman et al 2008;Sevastsyanovich et al 2008) indicate that backbone genes have different phylogenetic origins for different modules, and sometimes even for individual module genes (Fernandez-Lopez et al 2006). This suggests that plasmid innovation can occur, from time to time, by interacting with other plasmid backbones, which leads to insertion or replacement of backbone modules or to allelic replacements of individual genes.…”
Section: The World Of Conjugative Plasmidsmentioning
confidence: 99%
“…25 An analysis of their regulatory networks showed that these genetic elements have evolved sophisticated control mechanisms to alleviate the opposite demands of vertical and horizontal reproduction. The massive introduction of antibiotics has changed the conditions under which these genetic elements survive.…”
Section: Implications Of the Model And Future Researchmentioning
confidence: 99%